The application of in situ TEM on the grain boundary brittleness of precipitation-strengthened Ni-based superalloys: Recent progress and perspective - Zhou, Qian; Ding, Qingqing; Zhang, Yuefei; Wei, Xiao; Zhang, Ze; Bei, Hongbin (Frontiers in Metals and Alloys, 2022)
Due to their superior strength and oxidation resistance at high temperature, precipitation strengthened Ni-based superalloys are widely used in load-bearing hot components in energy generation systems, such as gas/steam engines in aircrafts or power plants, etc. However, brittleness originated from grain boundary (GB) in certain temperature range is one of the greatest deadlocks, which desperately restricts their thermal-mechanical processing capabilities and also industrial applications. Experimental and theoretical investigating the origin of the GB brittleness with aims to overcome it still attract many research efforts in the high temperature material field. It is desirable to understand the GB embrittlement mechanism by dynamically investigating the entire GB cracking process in real time under stress/temperature combination, which might be hardly revealed by traditional experimental/theoretical technologies. Current advances in high temperature mechanical testing systems, which can be operated in a transmission electron microscope (TEM), provide unique opportunities for in-situ exploring the mechanistic origins of GB brittleness of superalloys with the resolution up to atomic scale. Here, we first briefly give an overview of the phenomenon and current understanding on the GB brittleness followed by introducing the state of art techniques in in-situ TEM/mechanical testing system (MTS). In the end we will also discuss the potential application of in-situ TEM/MTS on the GB brittleness and a perspective overlook.